The Last Lincoln Conspirator : John Surratt's Flight from the Gallows. - Jampoler, Andrew (Naval Institute Press, 2011)
Despite all that has been written about the April 1865 assassination of President Abraham Lincoln, the story of John Surratt--the only conspirator who got away--remains untold and largely unknown. The capture and shooting of John Wilkes Booth twelve days after he shot Lincoln is a well-known and well-covered story. The fate of the eight other accomplices of Booth has also been widely written about. Four, including Surratt's mother, Mary, were convicted and hanged, and four were jailed. John Surratt alone managed to evade capture for twenty months and escape punishment once he was put on trial. I.